Characterization of kallikrein-related peptidase 4 (KLK4) mRNA expression in tumor tissue of advanced high-grade serous ovarian cancer patients - Gong, Weiwei; Liu, Yueyang; Seidl, Christof; Dreyer, Tobias; Drecoll, Enken; Kotzsch, Matthias; Bronger, Holger; Dorn, Julia; Magdolen, Viktor (PloS one, 2019)
Overexpression of several members of the kallikrein-related peptidase (KLK) family, including KLK4, has been reported in ovarian cancer tissue, consistent with the fact that elevated levels of KLK protein are often also found in serum and in effusion fluids of ovarian cancer patients. In the present study, we quantitatively analyzed KLK4 tumor tissue mRNA expression levels in a homogeneous cohort including 138 patients of advanced high-grade serous ovarian cancer (FIGO stage III/IV). Age as well as ascites fluid volume were found to be significantly associated with KLK4 mRNA expression levels. In univariate Cox regression analysis, the clinical factors residual tumor mass and ascites fluid volume represented univariate predictors for both overall survival (OS) and progression-free survival (PFS). Furthermore, elevated KLK4 mRNA expression levels were significantly linked with reduced OS (p = 0.001), but not with PFS. The results concerning the association of KLK4 mRNA expression with OS were validated in a publicly available Affymetrix-based mRNA data set from The Cancer Genome Atlas (n = 252) applying the Kaplan-Meier Plotter tool (p = 0.047). In multivariable analyses, elevated KLK4 mRNA values turned out as an additional, independent predictive marker for shortened OS (p = 0.006), whereas residual tumor mass, but not ascites fluid volume, remained an independent indicator for both OS and PFS (p < 0.001 and p = 0.002, respectively). The results of the present study, obtained in a well-defined, homogenous cohort of patients afflicted with advanced high-grade serous ovarian cancer, are in line with previous reports describing high KLK4 levels as an unfavorable marker in ovarian cancer patients.